Role of the Dopaminergic System in the Striatum and Its Association With Functional Recovery or Rehabilitation After Brain Injury - Verduzco-Mendoza, Antonio; Carrillo-Mora, Paul; Avila-Luna, Alberto; Gálvez-Rosas, Arturo; Olmos-Hernández, Adriana; Mota-Rojas, Daniel; Bueno-Nava, Antonio (Frontiers in Neuroscience, 2021)
Disabilities are estimated to occur in approximately 2% of survivors of traumatic brain injury (TBI) worldwide, and disability may persist even decades after brain injury. Facilitation or modulation of functional recovery is an important goal of rehabilitation in all patients who survive severe TBI. However, this recovery tends to vary among patients because it is affected by the biological and physical characteristics of the patients; the types, doses, and application regimens of the drugs used; and clinical indications. In clinical practice, diverse dopaminergic drugs with various dosing and application procedures are used for TBI. Previous studies have shown that dopamine (DA) neurotransmission is disrupted following moderate to severe TBI and have reported beneficial effects of drugs that affect the dopaminergic system. However, the mechanisms of action of dopaminergic drugs have not been completely clarified, partly because dopaminergic receptor activation can lead to restoration of the pathway of the corticobasal ganglia after injury in brain structures with high densities of these receptors. This review aims to provide an overview of the functionality of the dopaminergic system in the striatum and its roles in functional recovery or rehabilitation after TBI.